Novel type of red blood cell pyruvate kinase hyperactivity predicts a remote regulatory locus involved in PKLR gene expression. Issue 4 (3rd March 2014) - van, Brigitte Antoinette; Francois, Jerney Johanna Jeanette Maria; van, Wouter Willem; van, Annet Cornelia Wilhelmina; Rijksen, Gert; van, Hans Kristian Ploos; van, Richard
<x xml:space="preserve">Abstract</x> Red blood cell pyruvate kinase (PK‐R) is a key regulatory enzyme of red cell metabolism. Hereditary deficiency of PK‐R is caused by mutations in the PKLR gene, leading to chronic nonspherocytic hemolytic anemia. In contrast to PK deficiency, inherited PK hyperactivity has also been described. This very rare abnormality of RBC metabolism has been documented in only two families and appears to be without clinical consequences. Thus far, it has been attributed to either a gain of function mutation in PKLR or to persistent expression of the fetal PK isozyme PK‐M2 in mature red blood cells. We here report on a novel type of inherited PK hyperactivity that is characterized by solely increased expression of a kinetically normal PK‐R. In line with the latter, no mutations were detected in PKLR. Mutations in regulatory regions as well as variations in PKLR copy number were also absent. In addition, linkage analysis suggested that PK hyperactivity segregated independently from the PKLR locus. We therefore postulate that the causative mutation resides in a novel yet‐unidentified locus, and upregulates PKLR gene expression. Other mutations of the same locus may be involved in those cases of PK deficiency that fail to reveal mutations in PKLR. Am. J. Hematol. 89:380–384, 2014. © 2013 Wiley Periodicals, Inc.